PHYSIOCHEMICAL FACTORS AFFECTING GROWTH OF LACTOBACILLUS SALIVARIUS - R. Yasmeen; A. S. Hashmi; M. Athar; M. Tayyab; A. A. Anjum (Journal of Animal and Plant Sciences, 2021)
Lactobacillus salivarius (L. salivarius) is a probiotic bacterial species having a multiple range of therapeutic uses including antibacterial, antifungal and detoxifier. The present study was carried out to explore alternative and more effective medium for its growth. For this purpose, milk products (Skimmed Milk Powder: SMP and Fermented Whey Powder: FWP) supplemented with industrial waste (Corn Steep Liquor: CSL and Yeast Sludge: YS) were studied as alternative media for bacterial growth. Along with media components, physical conditions (Time, Temperature, pH, Agitation, etc.) were also optimized. Among both the milk products, FWP (2%) had shown the highest bacterial growth (11.7 + 0.17 log10 CFU/mL). Bacterial growth was improved by adding 0.3% CSL in both (FWP: 13.8 + 0.7 log10 CFU/mL and SMP: 12.8 + 0.03 log10 CFU/mL) media. FWP medium was comparatively better for growth of L. salivarius when 1 % YS was added (13.4 + 0.1 log10 CFU/mL). Optimum bacterial growth was achieved in both the media after 24 hours of incubation at 30 °C temperature, 6.5 pH and 200 rpm agitation. It was concluded that 2% FWP medium supplemented with 0.3% CSL, 1 % YS, 1% Glucose had proven to be better for growth of L. salivarius.
Keywords: Lactobacillus salivarius; optimization; milk products; industrial waste